(untitled) (Castilla. Estudios de Literatura, 2021)
This article reviews the sacramental plays written by Calderón de la Barca paying attention to the inclusion of books and readers in its argument, in what could be referred to as “reading scenes”. From the thorough study of the corpus of texts, it is possible to affirm that the insertion of read texts and physical volumes is not accidental, but that it responds to specific intentions thought by the author: to understand the sacramental plays as an extension of the mass, to stand ouy the Catholic faith in opposition to the reforms, to exalt the Eucharist and to show the repentance and need for redemption of mankind.